Modelling and analysing the interactive behaviour of an infusion pump - Campos, Jose; Harrison, Michael (Electronic Communications of the EASST, 2011)
This paper is concerned with the scaleable and systematic analysis of interactive systems. The motivating problem is the procurement of medical devices. In such situations several different manufacturers offer solutions that support a particular clinical activity. Apart from cost, which is a dominating factor, the variations between devices are relatively subtle and the consequences of particular design features are not clear from manufacturers’ manuals, demonstrations or trial uses. Despite their subtlety these differences can be important to the safety and usability of the device. The paper argues that formal analysis of the range of offered devices can provide a systematic means of comparison. The paper also explores barriers to the use of such techniques, demonstrating how layers of specification may be used to make it possible to reuse common specification. Infusion pumps provide a motivating example. A specific model is described and analysed and comparison between competitive devices is discussed.